Resynchronization of Lactating Dairy Cows at Open Pregnancy Diagnosis Based on the Presence or Absence of a Corpus Luteum: A Practical Approach - J. A. Sauls; J. S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2017)
Lactating Holstein cows in three herds were enrolled in a study at the time of nonpregnancy diagnosis. Cows were assigned to a resynchronization program based on ovarian structures determined by transrectal ultrasonography. Three resynchronization treatments were employed starting on the day of open diagnosis to test: (1) accuracy of ultrasound technician’s ability to identify a functional corpus luteum (CL); (2) whether an initial GnRH injection is required to start resynchronization when a CL is present at nonpregnant diagnosis (Short Synch: PGF2α— 24 hours — PGF2α— 32 hours — GnRH — 16 hours — timed artificial insemination [AI]); and (3) whether applying progesterone to cows without a CL as part of a traditional Ovsynch program (CIDR + Ovsynch: GnRH + CIDR insert — 7 days — PGF2α+ CIDR removal — 24 hours — PGF2α— 32 hours — GnRH — 16 hours — timed AI) would be equivalent to a standard Ovsynch program (same as CIDR-Ovsynch treatment but no CIDR was applied). Treatments produced similar proportions of pregnancies per AI, with a tendency for increased fertility when the first injection of GnRH was administered as part of a standard Ovsynch. The technician’s ability to detect a functional CL was more accurate when the CL visualized was actually functional (progesterone ≥ 1 ng/mL) than when it was not functional (progesterone<1 ng/mL). Although pregnancy outcomes tended to improve when cows were treated with Ovsynch compared with Short Synch, when a functional CL was accurately detected, pregnancy outcomes did not differ. Technician accuracy for detecting a functional CL is important for improving pregnancy outcomes when applying the Short Synch treatment.
Keywords: Corpus luteum; Resynchronization; CIDR insert; Gonadotropin-releasing hormone; Short Synch; PGF2α